Construction of UiO-66/Bi4O5Br2 Type-II Heterojunction to Boost Charge Transfer for Promoting Photocatalytic CO2 Reduction Performance - Li, Dongsheng; Zhu, Bichen; Sun, Zhongti; Liu, Qinqin; Wang, Lele; Tang, Hua (Frontiers in Chemistry, 2021)
One of the basic challenges of CO2 photoreduction is to develop efficient photocatalysts, and construction of heterostructure photocatalyst with intimate interface is an effective strategy to enhance interfacial charge transfer for realizing high photocatalytic activity. Herein, a novel UiO-66/Bi4O5Br2 heterostructure photocatalyst was constructed by depositing UiO-66 nanoparticles with octahedron morphology over the Bi4O5Br2 nanoflowers assembled from the Bi4O5Br2 nanosheets via an electrostatic self-assembly method. A tight contact interface and a built-in electric field were formed between the UiO-66 and the Bi4O5Br2, which was conducive to the photo-electrons transfer from the Bi4O5Br2 to the UiO-66 and form a type-II heterojunction with highly efficient of charge separation. As a result, the UiO-66/Bi4O5Br2 exhibited improved photocatalytic CO2 reduction performance with CO generation rate of 8.35 μmol h−1 g−1 without using any sacrificial agents or noble co-catalysts. This work illustrates an applicable tactic to develop potent photocatalysts for clean energy conversion.